Nationally-representative trends and geographic variation in treatment of localized prostate cancer: the Urologic Diseases in America Project - Cary, K. Clint (Prostate Cancer Prostatic Dis, 2015)
INTRODUCTION: Several treatment options for clinically localized prostate cancer currently exist under established guidelines. We aim to assess nationally-representative trends in treatment over time and determine potential geographic variation using two large national claims registries. METHODS: Men with prostate cancer insured by Medicare (1998–2006) or a private insurer (Ingenix database, 2002–2006) were identified using ICD-9 and CPT-4 codes. Geographic variation and trends in the type of treatment utilized over time were assessed. Geographic data was mapped using the GeoCommons online mapping platform. Predictors of any treatment were determined using a hierarchical generalized linear mixed model using the logit link function. RESULTS: The use of radical prostatectomy (RP) increased, 33% to 48%, in the privately insured i3 database, while remaining stable at 12% in the Medicare population. There was a rapid uptake in the use of newer technologies over time in both the Medicare and i3 cohorts. The use of laparoscopic assisted prostatectomy increased from 1% in 2002 to 41% in 2006 in i3 patients, while the incidence increased from 3% in 2002 to 35% in 2006 for Medicare patients. The use of neoadjuvant/adjuvant androgen deprivation therapy (ADT) was lower in the i3 cohort and has decreased over time in both i3 and Medicare. Physician density had an impact on type of primary treatment received in the New England region, however, this trend was not seen in the Western or Southern regions of the United States. CONCLUSION: Using two large national claims registries, we have demonstrated trends over time and substantial geographic variation in the type of primary treatment used for localized prostate cancer. Specifically, there has been a large increase in the use of newer technologies, (i.e. laparoscopic-assisted prostatectomy and IMRT). These results elucidate the need for improved data collection on prostate cancer treatment outcomes to reduce unwarranted variation in care.